2007
DOI: 10.1530/eje-07-0205
|View full text |Cite
|
Sign up to set email alerts
|

Psychological implications of Graves’ orbitopathy

Abstract: Patients with thyroid eye disease, Graves' orbitopathy (GO), often appear distressed and it is likely that features of the condition such as disturbances in visual function, orbital discomfort and alterations in facial appearance can impart significant psychological morbidity upon the patient, which in turn can be detrimental to their quality of life. When considering the psychological impact of GO, two elements of the disease are important. The disfiguring changes to the eyes and face can have a direct effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 32 publications
5
72
1
5
Order By: Relevance
“…As a result, our findings may not be fully comparable with those of other studies. However, the lack of a questionnaire that assesses the psychological status, as well as the general, clinical and psychosocial aspects of GD in all its complexity, as well as the response to medical and/or surgical treatment, is acknowledged in the international literature [2,18,28]. Surprisingly, our results showed that none of the patient characteristics were significantly associated with a higher HRQOL impairment after surgery.…”
Section: Discussioncontrasting
confidence: 57%
“…As a result, our findings may not be fully comparable with those of other studies. However, the lack of a questionnaire that assesses the psychological status, as well as the general, clinical and psychosocial aspects of GD in all its complexity, as well as the response to medical and/or surgical treatment, is acknowledged in the international literature [2,18,28]. Surprisingly, our results showed that none of the patient characteristics were significantly associated with a higher HRQOL impairment after surgery.…”
Section: Discussioncontrasting
confidence: 57%
“…3). It is well recognised that TED can have a profoundly negative impact on psychosocial functioning, self-esteem and quality of life (3)(4)(5)(6)(7). Therefore, it is particularly noteworthy that nearly three quarters of the responders felt that they did not receive help to deal with the psychological impact of the disease, and highlight the shortfall in psychological support of this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…TED has the potential to cause facial disfigurement and/or visual deficits, impacting on employment, hobbies and self-confidence, and frequently leading to a withdrawal from social interactions. Several previous studies have demonstrated a marked reduction in the quality of life of patients with TED as compared to the general population and patients with other chronic diseases (3)(4)(5)(6), to a degree that is often underappreciated by healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of debilitating clinical manifestations and complexity surrounding the treatment of TED on patients' physical and psychological wellbeing has been well recognised (27,28), the impact of quality of care on these patients' QOL is less discussed. Several surveys of patients with TED and health care professionals involved in the management of this disease have shown evidence for shortcomings in the provision of quality of care, which could contribute to the patients' poor QOL (21,(29)(30)(31)(32)(33).…”
Section: Quality Of Care Impacting On Qol In Patients With Tedmentioning
confidence: 99%